The carboboration of Me3Si-substituted alkynes and allenes with boranes and borocations. Issue 14 (16th September 2015) - Lawson, James R.; Fasano, Valerio; Cid, Jessica; Vitorica-Yrezabal, Inigo; Ingleson, Michael J.
Abstract : ArylBCl2 and aryl and vinyl containing borocations synthesised by electrophilic borylation effect the carboboration of TMS-substituted alkynes and allenes. Abstract : The 1, 1-carboboration of 1-Me3 Si-1-alkynes is the dominant reaction observed using [PhBCl(2-DMAP)][AlCl4 ], 1, and PhBCl2 electrophiles, with highly substituted vinyl pinacol boronate esters isolated post esterification. Other aryl and heteroaryl congeners of both1 and PhBCl2 have a limited scope in the 1, 1-carboboration of 1-Me3 Si-1-alkynes, with desilylboration more prevalent. PhBCl2 converts Me3 Si-substituted allenes to allylboranes via a formal 1, 3-carboboration with Me3 Si-migration. [Cl2 B(2-DMAP)][AlCl4 ] reacts with a number of 1-Me3 Si-1-alkynes by desilylboration, whilst with Me3 Si-ethyne a 1, 1-boroamination reaction proceeds, which with excess boron electrophile is followed by an intermolecular desilylboration to form a tricationic-borate. The use of excess 1-Me3 Si-1-propyne relative to1 (and a thienyl congener of1 ) formed 2-boradienes in low yields from the reaction with two equivalents of alkyne. Vinyl borocations ligated by 2, 6-lutidine of the general formula, [(vinyl)BCl(2, 6-lutidine)][AlCl4 ] formed 1-boradienes with 1-Me3 Si-1-alkynes.